Effects of Different Substrates on Rectangular Microstrip Patch Antenna for X-band - Khan, Imran; Geetha Devanagavi, D.; Sudhindra, K. R.; Prathibha, S.; C. Shruthi; Nirmala, S. (Asian Journal of Engineering and Applied Technology, 2018)
In this paper, the performance of Microstrip Patch Antenna (MSPA) is analyzed by changing the substrate materials. MSPA is designed to operate with the fixed dimensions of 32x26x1.6mm3 for three substrate materials. A comparison has been done in terms of reflection coefficient (S11), gain, efficiency (η), radiation pattern and cost. The simulated results show very good performance with TLC substrate as compared to FR4 and RT Duroid by showing good radiation efficiency for all the three bands viz 7.0, 9.6 and 10.8 GHz with the efficiency of 99%, 99% and 96% respectively, stable radiation patterns, gain of 1.32, 1.81 and 2.0 dB. FR-4 and RT Duroid produces two bands each of 8.4/ 9.6 GHz and 11.1/12.0 GHz respectively which shows a gain of 1.29/1.36 dB for FR4 and 1.04/7.95 dB for RT Duroid along with efficiency of 68%/ 60% and 96%/96% respectively with acceptable bandwidth. . The Antenna is simulated using HFSS simulator solution software.